Time of Change in Plato and Aristotle - Krása, Ondřej (My University, 2024)
When do things change? When do things have some characteristics? I try to answer these questions by looking at different solutions Plato and Aristotle presented in their works. The famous analysis of change from the second half of Plato’s Parmenides claims that change happens outside of time, at an “instant”. On the contrary, Aristotle in the Physics explicitly argues that all change occurs only in time. However, both Plato and Aristotle also provide other analyses of change. How to deal with this variety of explanations and tensions between them? In this paper, I argue that if we differentiate between several kinds of change, most of Plato’s and Aristotle’s analyses provide a thorough insight into the nature of change. For processes such as locomotion, change occurs exclusively within time. For changes where both the initial and final states occur only in time, such as a transition from motion to rest, change takes place in the ‘now’. However, for changes where both the initial and final states occur in both time and in the ‘now’ – for example, a qualitative change from being white to not being white – change does not occur in time nor in the ‘now’, but instead happens instantaneously.
Čas změny u Platóna a Aristotela
Keywords: Plato; Aristotle; Time; Change; Platón; Aristotelés; Změna; Čas